LEGO mindstorms NXT-G programming guide - Kelly, James F. (Technology in action press)
James Kelly’s LEGO MINDSTORMS NXT-G Programming Guide, second edition, is a fountain of wisdom and ideas for those looking to master the art of programming LEGO’s MINDSTORMS NXT robotics kits. This second edition is fully-updated to cover all the latest features and parts in the NXT 2.0 series. It also includes exercises at the end of each chapter and other content suggestions from educators and other readers of the first edition. LEGO MINDSTORMS NXT-G Programming Guide, second edition, focuses on the NXT-G programming language. Readers 10 years old and up learn to apply NXT-G to real-life problems such as moving and turning, locating objects based upon their color, making decisions, and much more. Perfect for those who are new to programming, the book covers the language, the underlying mathematics, and explains how to calibrate and adjust robots for best execution of their programming. Provides programming techniques and easy-to-follow examples for each and every programming block Includes homework-style exercises for use by educators. Gives clear instructions on how to build a test robot for use in running the example programs. Please note: the print version of this title is black & white; the eBook is full color. Robots and programs -- Program structure -- Hello world! -- Get movin’ -- Record and playback -- Make some noise! -- Wired! -- True or false? -- Feedback -- Wait for it! -- Round and round -- Decisions, decisions -- Stop it! -- Pick a card, any card -- Apples and oranges -- Inside or out? -- Yes? No? Maybe? -- Title = anything you like -- Basic rext -- Basic math -- Staying alive -- Your own filing cabinet -- Calibration -- Motoring -- Messages -- My block is your block.